Answers

2016-04-15T13:30:58+05:30
Given polynomial 6x² - 7x - 3
6x² - 7x - 3 = 0
⇒ 6x² +2x - 9x - 3 = 0
⇒ 2x(3x+1) - 3(3x+1) = 0
⇒ (3x+1) (2x-3) = 0
⇒ 3x+1 = 0   or   2x - 3 = 0
⇒ 3x = -1      or   2x = 3
⇒ x = -1/3     or     x = 3/2
∴ The zeroes are -1/3 and 3/2
Comparing  the polynomial  with general form ax² + bx +c = 0
Here, a = 6, b = -7 , c = -3
α = -1/3  and β = 3/2

α+β = -b/a
⇒ -1/3 + 3/2 = -(-7)/6
⇒(-2 + 9)/6 = 7/6
⇒ 7/6 = 7/6

αβ = c/a
⇒ -1/3 × 3/2 = -3/6
⇒ -3/6 = -3/6
Verified....
0